2009 24th International Conference Image and Vision Computing New Zealand 2009
DOI: 10.1109/ivcnz.2009.5378389
|View full text |Cite
|
Sign up to set email alerts
|

Detecting motion from noisy scenes using Genetic Programming

Abstract: A machine learning approach is presented in this study to automatically construct motion detection programs. These programs are generated by Genetic Programming (GP), an evolutionary algorithm. They detect motion of interest from noisy data when there is no prior knowledge of the noise. Programs can also be trained with noisy data to handle noise of higher levels. Furthermore, these auto-generated programs can handle unseen variations in the scene such as different weather conditions and even camera movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…images, which helped identify edges of objects and changes in colour and illumination. We used GP to evolve motion detection programs to recognize interesting motions from unstable background [4].…”
Section: Introduction and Methodologymentioning
confidence: 99%
“…images, which helped identify edges of objects and changes in colour and illumination. We used GP to evolve motion detection programs to recognize interesting motions from unstable background [4].…”
Section: Introduction and Methodologymentioning
confidence: 99%
“…In past, many modeling and background subtraction related techniques have been designed for motion detection. Moreover, to avoid manually coded motion detection system, different researchers used GP based automatically evolved systems [94][95][96][97][98][99]. It was observed that generally, the GP based evolved programs outperformed manually coded programs.…”
Section: Gp In Motion Detectionmentioning
confidence: 99%
“…Another difficult task in case of motion detection is to detect motion from noisy scene, when there is no information about the noise. Pinto et al [96] tackled this problem by using GP based approach in which motion detectors were generated during the testing phase on the basis of fitness function. In this approach, Gaussian noise was added in video [96] and showed better results for detecting motion in different environments.…”
Section: Gp In Motion Detectionmentioning
confidence: 99%
“…One of the advantages of GP is creativity as GP often finds excellent solutions which have never been thought by human experts. The adaptation of GP in image related tasks has been also successful, including image segmentation [17], edge detection [5], texture analysis [21], motion detection [16] and finding interest points [15]. On these tasks GP could achieve better or at least comparable performance without much domain knowledge.…”
Section: Introductionmentioning
confidence: 99%